Exploring Primary Student's Problem-Solving Ability by Doing Tasks Like PISA's Question - Rita Novita; Zulkardi Zulkardi; Yusuf Hartono (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2012)
Problem solving plays an important role in mathematics and should have a prominent role in the mathematics education. The term problem solving refers to mathematics tasks that have the potential to provide intellectual challenges for enhancing students' mathematical understanding and development. In addition, the contextual problem that requires students to connect their mathematical knowledge in solving mathematical situational problem is believed to be an impact on the development students' problem-solving ability. The tasks that have been developed by PISA meet both of these criteria. As stated by the NCTM, that problem-solving skill and ability should be developed to students when they were in primary school (K5-8), therefore, it is important to do an effort to guide students in developing problem-solving ability from primary school such as accustom students to do some mathematical solving-problem tasks. Thus, in this research we tried to investigate how to develop mathematical problem-solving tasks like PISA's question that have potential effect toward students' mathematical problem-solving abilities?. We used a formative evaluation type of development research as an mean to achieve this research goal. This type of research is conducted in two steps, namely preliminary stage and formative evaluation stage covering self evaluation, prototyping (expert reviews, one-to-one, and small group), and field test. This research involve four primary schools in Palembang, there are SD Muhammadiyah 6 Palembang, MIN 1 & MIN 2 Palembang, and SDN 179 Palembang. The result of this research showed that the mathematical problem-solving tasks that have been developed have potential effect in exploring mathematical problem-solving ability of the primary school students. It is shown from their work in solving problem where all of the indicators of problem solving competency have emerged quite well category. In addition, based on interview result from some students, known that they like to do such tasks because can improve their reasoning, creativity and thinking ability.